Effect of local dissociation on symmetry breaking in exclusion model constituted by bridge lane and input-output TASEPs. (November 2021) - Jindal, Akriti; Gupta, Arvind Kumar
Highlights: Local irreversible dissociation of particles on a complex topology of bridge lane coupled to input-output TASEPs is considered. Stationary system properties are analyzed under the mean-field framework. New symmetric and asymmetric phases emerge due to dissociation of particles. Local particle dissociations affect the bidirectional dynamics and spontaneous symmetry-breaking phenomena. Theoretical findings are validated using extensive Monte Carlo simulations. Abstract: Motivated by the dynamics of processive molecular motors in biological transport processes, we study the effect of local irreversible dissociation of two distinct species of particles moving along a bridge lane coupled to the input and output lanes governed by exclusion process. The boundary controlling rates of the particle in the bridge lane are determined self-consistently by the dynamics of the bridge and its feeding segments. A particle leaving the input lane is allowed to occasionally dissociate irreversibly from the exit site. The theoretical framework based on mean-field approximation is presented to understand how the local particle dissociations affect the bidirectional dynamics and spontaneous symmetry-breaking phenomena. Explicit phase boundaries and density profiles are obtained to analyse the steady-state behavior of the overall system. It has been observed that change in amplitude of dissociation rates leads to non-monotonic behavior of stationary phase diagrams and significant modifications in the dynamic properties. The emergence of new symmetric and asymmetric phases is reported under the symmetry of boundary controlling parameters and dissociation rates. Simple physical arguments are presented to explain the stationary properties of the system. Extensive Monte Carlo simulations are performed to test the validity of theoretical outcomes.